Investigation of interface healing behavior in 1.5 wt.%CNTs/Al–4Cu–1Mg composite solid-state bonding joints influenced by surface processing marks - Zuo, Guoliang; Bai, Yu; Shi, Shuyan; Tan, Zhanqiu; Fan, Wenxue; Li, Zhiqiang; Hao, Hai (Journal of materials research and technology, 2024)
Joint units processed by milling and grinding, which varied in surface processing marks, were used in solid-state bonding experiments to study how these marks affect the healing behavior of CNTs/Al composite bonding interfaces. The results showed that these machining marks significantly impact interface healing, as evidenced by the shapes and sizes of the interface oxides after bonding, and by the magnitude of forces and displacements transmitted from macroscopic deformations to microscopic interfaces. The healing process involves gap closure, oxide layer fracturing, fresh metal extrusion, and oxide dissolution. CNTs and their byproduct Al4C3 play a crucial role in this process. They pin the grain boundaries and interfaces, providing multiple deformation anchorage points, which not only cause the interface oxide layer to fracture into fine oxide fragments but also effectively suppress grain coarsening at high temperatures. Their dispersed distribution in the Al matrix offers massive phase boundaries. Combined with the high-density grain boundaries in the ultrafine CNTs/Al composites, this facilitates atomic short-circuit diffusion, thereby accelerating the dissolution of oxide inclusions at the interface. Enhancing the precision of surface machining can effectively reduce oxide inclusions at the bonding interface and promote interface healing, while redundant processes should be avoided. The strength of the solid-state bonding joints under precision grinding has reached 376 MPa, exceeding 90% of the raw material strength, achieving high-efficiency seamless bonding.